Senieji (Old) Trakai: A Case Study of Environmental Transformation - Kuncevičius, Albinas; Merkytė, Inga; Poškienė, Justina; Prapiestienė, Regina; Vengalis, Rokas; Vėlius, Gintautas; Volungevičius, Jonas (Archaeologia Lituana, 2018)
[full article and abstract in Lithuanian; abstract in English]Extensive works of environmental transformations were carried out in the main administrative centers of the Grand Duchy of Lithuania during the 13th–14th c. These processes reveal the potential of the Gediminid ruling dynasty. Development processes in the 13th–14th c. Vilnius are being researched and give essentially new data on the genesis of the capital. Nevertheless, similar works, which were carried out in the other administrative centers of the State (the historical capitals Kernavė and Trakai) are not investigated. This article seeks to present the case of the Senieji (Old) Trakai Castle and its settlement regarding the scale, character and presumable chronology of environment transformations. It seeks to systemize the previously obtained data on Senieji Trakai as well as to present the results of geophysical research, small-scale archaeological excavations and soil analysis, which were obtained in 2018.
Keywords: Senieji (Old) Trakai; geophysical methods; magnetometer; ground penetrating radar; soils